Clinical Observation of Macroamylasemia in Splenosis Due to the Posttraumatic Splenectomy - Gubergrits, Natalya B; Zubov, Aleksandr; Golubova, Oksana; Fomenko, Pavel; Byelyayeva, Nadezhda (JOP. Journal of the Pancreas, 2014)
Context Article analyzes current data on macroamylasemia and splenosis, their etiology and diagnostics in particular. Case Report Authors presented their own clinical observation of a young woman who was diagnosed to have macroamylasemia on the background of splenosis due to the splenectomy after blunt abdominal injury. Conclusion This is the first time such a combination of macroamylasemia on the background of splenosis has been described in the literature. Image: Spiral CT of abdomen and retroperitoneum